Limits to climate change - Parkash Chander; Henry Tulkens (Fondazione Eni Enrico Mattei (FEEM), 2001)
The paper proves the existence and uniqueness of a noncooperative steady state in the context of a model of climate change. It also explores the possibility of cooperation and attainment of an optimal steady state. It is shown that the problem is similar to that in the static model (Chander and Tulkens (1997)).
Keywords: C6; C71; C73; H22; H77; Q2; 330; Climate change; dynamic models; steady states; optimality; cooperation; Klimawandel; Klimaschutz; Internationale Umweltpolitik; Dynamisches Spiel; Theorie